DIFFERENT TECHNIQUES OF FORMULATION AND EVALUATION OF MUCOADHESIVE MICROSPHERES - PANDEY SHIVANAND (International Journal of Pharma and Bio Sciences, 2010)
Drug delivery systems (DDS) that can precisely control the release rates or target drugs to a specific body site have an enormous impact on the health care system. Carrier technology offers an intelligent approach for drug delivery by coupling the drug to a carrier particle such as microspheres, nanoparticles. Which modulates the release and absorption characteristics of the drug? Micro spheres constitute an important part of these particulate DDS by virtue of their small size and efficient carrier characteristics. However the success of these novel DDS is limited due to their short residence time at the site of absorption. It would, therefore, be advantageous to have means for providing an intimate contact of the DDS with absorbing membranes. It can be achieved by coupling mucoadhesion characteristics to microspheres and developing novel delivery systems referred to as “mucoadhesive” microspheres.